Cognitive-motor interference in multiple sclerosis revisited: a dual-task paradigm using wearable inertial sensors and the Paced Auditory Serial Addition Test - Kremer, Lea; Schreff, Lucas; Hamacher, Daniel; Oschmann, Patrick; Rothhammer, Veit; Keune, Philipp M.; Müller, Roy (Frontiers in Neurology, 2025)
IntroductionMultiple sclerosis (MS) is a chronic autoimmune disease affecting the central nervous system, leading to motor and cognitive impairment. These impairments become especially evident during dual-tasks, such as walking while performing a cognitive activity. Previous research has highlighted changes in gait-specific parameters during dual-tasks, but the cognitive component remains underexamined in MS. This study aims to expand on prior findings by using wearable inertial sensors and the Paced Auditory Serial Addition Test (PASAT) to evaluate the effects of dual-tasks on gait and cognitive performance in persons with MS (PwMS) compared to healthy controls.MethodsEighty-six adults (54 PwMS and 32 healthy controls) participated. PwMS were further divided into groups with lower (MS_LCP) and higher (MS_HCP) cognitive performance based on performance on the Symbol-Digit-Modalities Test (SDMT). Gait parameters were assessed using wearable inertial sensors during single- and dual-task 3-min-walking. Statistical analyses compared gait and cognitive performance across conditions and groups.ResultsUnder dual-task conditions, PwMS showed significant changes in all gait parameters, including reduced walking speed, stride length, percentage of swing phase and toe clearance, and increased stride time and percentage of stance phase compared to single-task condition. However, under dual-task condition in PwMS only walking speed, stride length and stride time differed from healthy controls. MS_LCP exhibited greater changes in both gait and PASAT performance than MS_HCP and healthy controls. While MS_HCP showed gait parameters comparable to healthy controls during single-tasks, deficits became apparent during dual-tasks. Correlations revealed strong associations between SDMT and PASAT scores but weak links between cognitive and self-reported measures.DiscussionThe findings confirm that dual-task conditions exacerbate gait impairments in PwMS, particularly in those with lower cognitive performance. The use of PASAT as a dual-task cognitive challenge was feasible and had a considerable influence on gait. Results support the capacity sharing theory, suggesting that limited cognitive resources are redistributed between tasks under dual-task conditions.